Kajian Literatur Pengaruh Green Marketing terhadap Keputusan Pembelian - Sahrir, Ahmad (Jurnal Manajemen dan Inovasi (MANOVA), 2018)
Environmental damage is clearly visible and is a common enemy, the government and companies must have a harmonious goal to overcome the damage that has occurred and prevent greater damage later on the effect. Green marketing marketing strategy is a concept that encompasses all marketing activities developed to stimulate and maintain environmentally friendly consumer behavior, forming a good image for consumers so as to influence consumer purchasing decisions. The purpose of this study is to strengthen previous research which states that green marketing influences consumer purchasing decisions. Data collected through the method of literature review, using books, journals relevant to the theme of the discussion. The results of the study prove that green marketing has a significant influence on purchasing decisions